Espaços livres públicos em Belo Horizonte: um estudo das relações estabelecidas entre o uso e a forma - Natália Mara Arreguy Oliveira (2012)
The use of Belo Horizonte`s free spaces followed the development of the city. Some had already been foreseen in the original project proposed by the engineer Aarão Reis and by the Construction Commission of New Capital (responsible for the original urban design) and others were created later, during the occupation of the peripheral areas. Even though it was designed in previous historical contexts than the current one, the free spaces disposed in the central area (located within Avenida do Contorno, germinal core of Belo Horizonte) maintained usage conditions also suitable to the activities that appeared with the conditions of contemporary life. On one hand, what can be seen in Belo Horizonte, at least, being the focus of study of this paper is that people have adapted, maintaining the practice of their social interaction activities in places that already exist. On the other hand, it can be noted that some public spaces that were designed in the past to house a lifestyle from that historical moment - that contained activities such as footing, band presentations and civic parades - had become obsolete and, in some cases, are no longer frequented, depending on the intervention of the Public Authorities to be reinstated as free space for public use effective. Observing the squares and parks that are still alive after many decades after the inauguration, it is believed that it is necessary to investigate the project aspects and the solutions of the spatial conditions found in these places that allowed the maintenance of these places in the daily life of those born in Belo Horizonte. Through the case studies, it is expected to understand which aspects are important to the construction of a "space essence" and apply them on reflections about the direction of the future free space project. Faced with this challenge, the admitted assumption is that to be suitable to the endless possibilities of use demanded by the contemporary society, the free urban space should allow both the coexistence of diversity of users and the plurality of usage. Therefore, it is understood that both the study of the relationship of the user with the public space and the understanding of the shape of the place are fundamental to the analysis of the occupation dynamics of these places.In this context, this paper unfolds in the study of the importance of quality of the project from both the micro-region occupied by the user when interacting with the urban space and the relevance of the shape of public space resulted from the juxtaposition / superposition of the small portions occupied. It has been a hypothesis that the relationship ofthe user with the space is as relevant to the liveliness of public space as it is the connection of this object (square, park, etc.) with the urban context.